PENERAPAN METODE PEMBELAJARAN PEER ASSISTED LEARNING (PAL) PADA SKILLS LAB DAN OBJECTIVED STRUCTURED CLINICAL EXAMINATION (OSCE) : A LITERATUR REVIEW - Kusdhiarningsih, Betty; Sundari, Sri (Jurnal EDUNursing, 2019)
Objective Structured Clinical Exam (OSCE) is a method used to evaluate the learning outcomes of clinical skills of the students which are objective and comprehensive. The aim of the OSCE is to introduce the clinical situations and conditions on the actual field to the students. One of the methods to increase the students? passing rate is the Peer Assisted Learning (PAL) learning system. PAL is a learning method, which uses peers who are appointed as tutors to help tutee (group friends, peers) in a small group. This study aims to describe the use of PAL in Skills Laboratorium and OSCE. The results of the literature review show that most anxiety can be reduced by using the PAL method, as compared to other learning methods, so that it directly affects the value, increases the level of confidence, and makes it easier for students to learn.  This method is expected to be applied in laboratorium skill learning for OSCE preparation, because of its very positive influence. Keyword:Peer Assisted Learning, OSCE, Skills Lab